Pengembangan Karakter Rasa Keadilan Berbasis Permainan Tradisional Untuk Anak Usia 7-9 Tahun - Mariska Santi; Gregorius Ari Nugrahanta (Universitas Muhammadiyah Jakarta, 2023)
Parents have expressed concern over the recent crisis in children's sense of justice. Various efforts have been made to overcome this problem, one of which is character development from an early age. This study aims to develop a guidebook based on traditional games to foster a sense of justice in children aged 7-9 years. For this purpose, the Research and Development (R&D) ADDIE type research methodology was employed. This study involved ten teachers for the purposes of needs analysis, ten validators with expertise from various related fields, and eight children as subjects in a limited trial. The study's findings show that: 1) the traditional game-based justice character education guidebook for children aged 7-9 years is appropriate and developed based on the ADDIE stages, 2) through expert judgment carried out by the validator, the guidebook obtains an average score of 3.77 with the qualification